Investigating Labor Pain Coping according to Irrational Beliefs in Pregnancy - Farideh Khavari; Nahid Golmakani; Azadeh Saki; Hamid Reza Aghamohammadian Sherbaf (Mashhad University of Medical Sciences, 2017)
Introduction: childbirth self-efficacy points to the beliefs of a person about ability to use certain coping behaviors during labor. Studies showed that when people have false beliefs, use less of their abilities. This study was performed with aim to investigate the relationship between irrational beliefs and childbirth self-efficacy. Methods: This descriptive-correlational study was conducted on 702 pregnant women in 35-39 weeks of gestation, low risk, and third pregnancy referring to the health centers of Mashhad in 2015. Data collection tools included: Demographic and Midwifery questionnaire, Jones' Irrational Beliefs and Childbirth Self-efficacy Inventory. The form of subjects' selection and Demographic and Midwifery questionnaire was completed by the researcher through interview and data recorded in the file, and Irrational Beliefs and Childbirth Self-efficacy Inventory were completed by research's units in the presence of the researcher. Data were analyzed using SPSS software (version 16) and spearman correlation, linear regression and general linear models. P<0.05 was considered significant. Results: According to the results, mean score of irrational beliefs was 357.7±34.8 and 439.2±99.2 for childbirth self-efficacy. Childbirth self-efficacy had a significant direct linear relationship with irrational beliefs of emotional irresponsibility and dependency and had a significant reverse linear relationship with high self-expectations (P<0.001). Conclusions: Irrational beliefs such as emotional irresponsibility, dependency and self-expectation can predict coping with labor pain in pregnant women.